Mid-trimester rupture uterus: case series - Kapur, Aishwarya; Prasad, Sudha; Gupta, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterine rupture is an obstetric catastrophe with significant maternal and fetal morbidity and mortality which occurs mainly in the third trimester of pregnancy or during labour, especially in previously scarred uterus. The occurrence of rupture in first and second trimester in women with unscarred uteri is quite rare. We report two cases of rupture uteri managed in our centre at 24 and 26 weeks gestation in women with unscarred uteri. First case was G3P1L1A1, 24 weeks with epigastric pain, stable vitals, epigastric tenderness, USG inconclusive, CT scan showed out pouching of amniotic sac through fundus. Laparotomy done, there was 8-9 cm fundal rupture extending between cornua, uterine repair done. Second case was G3P1L1A1 26 weeks with abdominal pain, stable vitals, corresponding fundal height, head engaged, USG revealed outpouching amniotic sac at the fundus. Laparotomy performed, there was 10 cm rent extending trans-fundal, uterine repair done. Unscarred uterine rupture, especially in early pregnancy is a rare event, posing significant difficulty in diagnosis. Uterine rupture should be first ruled out in all pregnant women presenting with acute abdomen irrespective of gestational age. Search for non-gynaecological causes can delay crucial obstetric intervention that can lead to loss of obstetric function, morbidity and mortality.